(3TPG GdYQa GdfOi aj PcQ JQGLe Hfi YOis - (3eMeO Hf eMeO Hf MGeO Hf eMeO GdLQLGhj GdeQGZj,J (B1355 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eMi eG Hdi ef Qeje GdYXGe s
(3BNQgG (B:s
(3hgGgfG Lfi Gdbdf hGdMeO ddg QH GdYGdejf s
(3HBNQgG JbQjXGJs
(3hGdfSNI JUhjQgG ZjQ LjO ai GdebOegs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B204s
Keywords: (3GdJGQjNs